Publisher Correction: Mergeable nervous systems for robots - Nithin Mathews (Nature Portfolio, 2017)
The original version of this Article contained an error in the author contributions section, whereby credit for design of the experiments was not attributed to N.M. This error has now been corrected in both the PDF and HTML versions of the Article.